Action research, power and responsibility : the predicament and potential of New Zealand community groups : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy, Massey University, Albany, Auckland, New Zealand - Cervin, Carmel Frances (Massey University, 2001)
This thesis tells the story of the action research projects of three community groups: The West Auckland Women's Centre, Homebuilders Family/Whanau Support Scheme, and the Autistic Association of New Zealand Inc., Auckland Branch. The projects focused on addressing specific injustices identified by each community group. Through participating in three concurrent projects, significant insights into the process, context, and key themes of action research are presented. The methodology discussion integrates the literature review with practical examples drawn from these projects. This enables critical observations on action research to be identified and explored in a grounded substantive manner. Key themes include: ethical implications of an academic researcher working with community groups, particularly in terms of power dynamics; recognition and validation of the expertise shared within the groups; and the necessity of trusting in the evolving nature of the action research process. Comparisons between the groups are written sensitively, honouring each group and their processes. The West Auckland Women's Centre project consisted of qualitative research exploring retirement income and issues around unpaid work for women. The project was undertaken as part of the Women's Centre's role as an advocate on issues affecting women. Homebuilders began with a story-telling project that sought to address a lack of understanding about their work in their community. However their focus shifted to a new project on Rural Living Standards following concerns raised by Homebuilders workers regarding the difficulties faced by families they were working with. The project developed in to a comprehensive survey on family household living standards, using a participatory process with the involvement of a large number of interested people from the community. The results of this survey are being fed back into the community to raise awareness regarding the spread of living standards and income issues in the local community. The Autistic Association project consisted of a comprehensive survey of all Auckland branch members to identify needs and gaps in services for families with a family member with Autism or Aspergers. The survey was then used, and continues to be used, to lobby and educate funding providers and government agencies regarding the services needed. The National Autistic Association is, at the time of completing this thesis, running the survey nationally. Finally this thesis explored the predicament of community groups acting as advocates for families in a context where funding providers set all the rules for 'negotiation' and highlighted the potential of community group action research projects for power reversals and enhancing democracy.
Keywords: Community organisation; Social problems; Community surveys; Fields of Research::370000 Studies in Human Society::370100 Sociology